Metodología de diseño electrónico aplicado en circuito detector de agua - Díaz Montealegre, Leidy Catherine; López Téllez, Alexander (Redes de Ingeniería, 2018)
With the design methodology of electronic circuits in the laboratory, trainees are created an interest to observe and explore as small scientists the characteristics of analog and digital electronics, having as a fundamental principle the theoretical and mathematical recognition of the law of ohm, the theorems and principles of different scientists such as Nikola Tesla, Thomas Edison and Georg Simon Ohm, guided by a facilitator in the approach, development and solution of the problem, and thus, be able to create prototypes or products of science, technology and innovation using research methodologies . This article shows the design, the construction of analog-digital electronic circuits and the procedures they perform to obtain experimental information, focused on the project called "Moisture Detector" that allows, as its name indicates, to detect humidity by checking electrical continuity and short circuit, thus when greater humidity there is less resistance to current flow.